2022
DOI: 10.1038/s41597-022-01126-7
|View full text |Cite
|
Sign up to set email alerts
|

gga-miRNOME, a microRNA-sequencing dataset from chick embryonic tissues

Abstract: MicroRNAs (miRNAs) are small non-coding RNA molecules, with sizes ranging from 18 to 25 nucleotides, which are key players in gene expression regulation. These molecules play an important role in fine-tuning early vertebrate embryo development. However, there are scarce publicly available miRNA datasets from non-mammal embryos, such as the chicken (Gallus gallus), which is a classical model system to study vertebrate embryogenesis. Here, we performed microRNA-sequencing to characterize the early stages of trun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…miRNAs are small non-coding RNA molecules, which are key players in gene expression regulation [ 55 ]. 3′-UTRs of mRNA are primarily targeted by miRNA molecules that form complex gene regulatory networks [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are small non-coding RNA molecules, which are key players in gene expression regulation [ 55 ]. 3′-UTRs of mRNA are primarily targeted by miRNA molecules that form complex gene regulatory networks [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent work from our group showed that different miRNA species are expressed in the PSM and in the forelimb distal cyclic domain. These tissues have very different EC periodicities (discussed below), which suggests that miRNAs may play a role in establishing different paces of the EC ( Duarte et al, 2022 ).…”
Section: Gene Expression Oscillationsmentioning
confidence: 99%